PENGARUH PENGETAHUAN AKUNTANSI, PENDIDIKAN PEMILIK, OMZET USAHA, DAN MASA MEMIMPIN PERUSAHAAN TERHADAPPENGGUNAAN INFORMASI AKUNTANSI (STUDI EMPIRIS PADA UMKM DI KABUPATEN KAMPAR) - Arif Rahman; Kamaliah Kamaliah; Adhitya Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about (1) The influence of accounting knowledge on the use of accounting information (2) The influence of owner education on the use of accounting information(3) The influence of business turnover on the use of accounting information and (4) The manager/owner’s length of time in managing on the use of accounting information. Population in this research is UMKM in Kampar district.. The method that used to the sample selection was purposive sampling method. The number of samples in this research were 117 respondents. The type of data used in this study is primary data.Data collection techniques used survey techniques by distributing questionnaires.Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 22.0 for Windows as data processing software program.Results of hypothesis test using statistical t-test showed the significant value of accounting knowledge variable 0.000< 0.05, which means that H1accepted, the owner education variable 0.072> 0.05, which means that H2not accepted, business turnover variables 0.02< 0.05, which means the H3 accepted, and manager/owner’s length of time in managing variables 0.265 > 0.05 which means that H4not accepted.Keywords : micro small and medium enterprises, the use of accounting information , accounting knowledge, owner education, business turnover and manager/owner’s length of time in managing.